The Mediating Role of Soft Skills in the Effects of Perceived Campus Support and Industrial Internship Experience on Graduates’ Work Readiness: From the Department of Informatics and Computer Engineering, Universitas Negeri Makassar - AriyaniZulkarnain; Faisal Syafar; Anas Arfandi (Jurnal Pendidikan Terapan, 2026)
The increasing demand for work-ready graduates in the digital era has encouraged higher education institutions to strengthen academic support and industrial internship programs. However, limited studies have examined the mediating role of soft skills in the effects of perceived campus support, industrial internship experience, and graduates' work readiness, particularly in the context of informatics and computer engineering higher education. This study aims to examine the effects of perceived campus support and industrial internship experience on graduates' work readiness, with soft skills serving as a mediating variable among graduates of the Department of Informatics and Computer Engineering, Universitas Negeri Makassar. This study employed a quantitative approach using an ex post facto research design. A total of 220 graduates were selected through proportional random sampling. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that perceived campus support and industrial internship experience have positive and significant effects on soft skills. Industrial internship experience and soft skills also have positive and significant effects on graduates' work readiness, whereas perceived campus support has no direct effect on work readiness. Furthermore, soft skills significantly mediate the  effects perceived campus support, industrial internship experience, and graduates' work readiness. The novelty of this study lies in explaining the mediating role of soft skills in the effects of perceived campus support and industrial internship experience on graduates' work readiness within the context of informatics and computer engineering higher education. The findings imply that higher education institutions should strengthen campus support systems and improve the quality of industrial internship programs to foster graduates' soft skills and enhance their work readiness.